LONG-TERM NEUROLOGICAL CONSEQUENCES OF ENVIRONMENTAL AND LIFESTYLE FACTORS: MECHANISMS, RISK MODIFIERS, AND PREVENTIVE STRATEGIES IN BRAIN HEALTH (Global Conference on Medical and Health Sciences, 2026)
Environmental and lifestyle factors play a critical role in shaping long-term neurological health, influencing the development and progression of a wide range of neurological disorders. Increasing evidence suggests that chronic exposure to environmental stressors—such as air pollution, toxins, and socioeconomic conditions—combined with lifestyle factors including diet, physical activity, sleep patterns, and substance use, significantly affects brain structure and function. These influences operate through complex biological mechanisms involving oxidative stress, inflammation, epigenetic modifications, and neurovascular dysfunction.
Keywords: Environmental factors; Lifestyle; Neurology; Neurodegeneration; Inflammation; Oxidative stress; Brain health; Risk factors